Intracellular T lymphocyte cytokine profiles in the aqueous humour of patients with uveitis and correlation with clinical phenotype - Hill, T (Blackwell Science Inc, 2005)
This study aimed to investigate whether T cells in aqueous humour are different in different types of uveitis and correlate with clinical phenotype. Patients with clinically different types of uveitis, but all displaying active anterior uveitis, were phenotyped and samples of aqueous humour (AH) and peripheral blood (PB) collected. Cells from AH and PB were separated by centrifugation and by density gradient centrifugation (to obtain mononuclear cells PBMC), respectively. Cells were activated with PMA and ionomycin in the presence of Brefeldin A, stained for surface markers and intracellular cytokines, and analysed by flow cytometry. The cytokine profile was correlated with the clinical phenotype. Increased percentages of interleukin (IL)-10(+)-, but not interferon (IFN)-γ(+) T lymphocytes were found in AH compared with PB in patients with acute anterior uveitis (AAU), FHC or chronic panuveitis (PU). There was a trend towards elevated levels of IL-10(+) T cells in AH from patients with FHC compared with AH from acute uveitis and panuveitis patients. Increased levels of IL-10(+) T cells in AH compared with PB were also found in samples from patients with isolated uveitis, but not those with associated systemic disease. Levels of cytokine-positive T cells were not associated with the use of topical steroids or to the severity of the anterior uveitis. While type I cytokine-producing T lymphocytes are present in AH during AU, the presence of increased proportions of IL-10(+) T lymphocytes in AH from patients with uveitis may be indicative of an anti-inflammatory mechanism that may influence the type and course of ocular inflammation in these patients.